El pianista - Polanski, Roman, 1933-; Brody, Adrien; Kretshmann, Thomas; Kilar, Wojciech; Edelman, Pawel (Leader Music, 2006)
Narra la odisea del músico judío-polaco Wladyslaw Szpilman para sobrevivir al holocausto en Varsovia.